Protection of natural Wetland within development area: a case study of Tasik Melati - Ali, Maisarah; Mohd. Radzi, Noor Shakilah; Jusoff, Kamaruzzaman (International Energy and Environment Foundation, 2007)
Wetlands provide an important ecological function that contributes to watershed functions, most notably in pollutant removal, flood attenuation, groundwater recharge and discharge,shoreline protection, and wildlife habitat. However, despite of the many watershed services wetlands provide, the pressure from the development of a city is great. This research is carried out to identify the threats that will affect wetlands and the surrounding area undergoing development by using several methodologies, namely observations, photograph analysis and interviews. The area chosen for the study is a wetland in Tasik Melati near the township of Kangar Perlis which is located in the Northern Peninsular Malaysia. The area was originally fresh swamp forest and in 2001 has been designated as recreational area. Currently 50.4 acres has been developed and another 33.3 acres is for future development. This event more or less provides an attestation to the function and the role of this wetland and the impacts that may occur if it were to undergo any changes. There is a need to compromise between conservation and development as conservation of wetlands is of great significance in preventing flooding.